Ethical and Professional Challenges Encountered by Laboratory Genetic Counselors. Issue 4 (16th November 2014) - Groepper, Daniel; McCarthy Veach, Patricia; LeRoy, Bonnie S.; Bower, Matthew
Abstract: Laboratory‐based genetic counseling is a growing and yet under researched specialty. In this study, 111 laboratory‐based genetic counselors employed in various settings (commercial, academic, etc.) completed an online survey assessing demographics and frequency of encountering 16 domains of ethical and professional challenges encountered by clinical genetic counselors defined previously by McCarthy Veach et al. and validated by Bower et al. Forty‐nine of the laboratory genetic counselors also provided anecdotes of particularly challenging situations and strategies for their resolution. Most respondents had less than 5 years' experience as laboratory counselors (71 %), worked full‐time (75 %) in industry‐based laboratories (91 %) with a focus on molecular diagnostics (84 %), and had limited patient contact (91 %). Similar to clinical counselors, every ethical and professional challenge was endorsed as occurring frequently by some respondents. The most common frequently occurring domains for the sample were: facing uncertainty, time and financial resource allocation, attaining and maintaining proficiency, and informed consent. Content analysis of respondents' anecdotes yielded themes that most commonly concerned: professional identity issues, value conflicts, confidentiality, and colleague error. One unique domain labeled professional communication (educating professionals with limited genetics knowledge), and three salient categories within the professional identity domain ‐ gatekeeping, conflicts of interest, and professional image ‐ were extracted from the anecdotes. The most prevalent strategy for resolving challenging situations was inform health care professional . Results suggest laboratory‐based genetic counselors generally face similar ethical and professional challenges as clinical genetic counselors but their exact nature and relative frequency differ. These findings contribute to a greater understanding of common and unique experiences of genetic counselors in different professional specialties.